2021
DOI: 10.1371/journal.pmed.1003632
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of splenic accumulation and colocalization of immature reticulocytes and Plasmodium vivax in asymptomatic malaria: A prospective human splenectomy study

Abstract: Background A very large biomass of intact asexual-stage malaria parasites accumulates in the spleen of asymptomatic human individuals infected with Plasmodium vivax. The mechanisms underlying this intense tropism are not clear. We hypothesised that immature reticulocytes, in which P. vivax develops, may display high densities in the spleen, thereby providing a niche for parasite survival. Methods and findings We examined spleen tissue in 22 mostly untreated individuals naturally exposed to P. vivax and Plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
88
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(98 citation statements)
references
References 79 publications
1
88
0
Order By: Relevance
“…In a nonhuman primate P. vivax model, spleendependent expression of molecules mediating adhesion to human splenic fibroblasts has been described [36], suggesting the presence of a parasite phenotype that may favor splenic accumulation. Finally, very recent data suggest that immature reticulocytes accumulate in the human spleen providing a favorable niche for P. vivax accumulation [11]. We now show evidence supporting splenic tropism and splenic accumulation of P. vivax very early in infection.…”
Section: Plos Medicinesupporting
confidence: 76%
See 1 more Smart Citation
“…In a nonhuman primate P. vivax model, spleendependent expression of molecules mediating adhesion to human splenic fibroblasts has been described [36], suggesting the presence of a parasite phenotype that may favor splenic accumulation. Finally, very recent data suggest that immature reticulocytes accumulate in the human spleen providing a favorable niche for P. vivax accumulation [11]. We now show evidence supporting splenic tropism and splenic accumulation of P. vivax very early in infection.…”
Section: Plos Medicinesupporting
confidence: 76%
“…In these studies, few or no parasites were identified in the brain or intestines, whereas the bone marrow and liver sinusoids were major tissue reservoirs for P. vivax schizonts and gametocytes [9]. An apparent predilection for the spleen, bone marrow, and liver is consistent with biomarker evidence of a hidden biomass of parasite accumulating in non-endothelial lined spaces [10] and the strict reticulocyte tropism of this species, which may promote concentration in organs in which immature reticulocytes accumulate [4,11]. Nonetheless, this hypothesis is challenging to confirm in life, where these processes are largely inaccessible to evaluation.…”
Section: Introductionmentioning
confidence: 60%
“…Recently, Kho et al. described the accumulation of biomass due to medium to high CD71 + expressing reticulocytes as well as non-phagocytosed parasites, thus providing another shelter for the parasite’s survival and replication, contributing to splenomegaly ( Kho et al., 2021 ). We also demonstrated the presence of free parasites in the spleens during the murine model of B. microti infection ( Djokic et al., 2018a ); however, neither RBC aggregations nor biomass accumulation was observed ( Srivastava et al., 2015 ).…”
Section: Disease and Symptomsmentioning
confidence: 99%
“…Splenic tropism is the highest in P. vivax infections with more than 98% of asexual-stage parasites. This may suggest that chronic malaria could be due to the infection of the spleen, instead of blood infection solely [ 90 , 91 ]. Infected erythrocytes deformability can also be observed in P. ovale and P. cynomolgi infections [ 87 ].…”
Section: Characteristics and Pathology Associated With Individual Zoonotic Plasmodium Speciesmentioning
confidence: 99%